Collaboration of the Method of Iqro’’ and Tsaqifa for Al-Qur’an Learning in the Group of Hajj and Umrah Guidance at Karanganyar Regency - Naj'ma, Dinar Bela Ayu (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
This research aims to elaborate the collaboration between Iqro’’ and Tsaqifa method for Qur’an learning in Hajj and Umrah Guidance group which handled by the council of hajj and umroh of the great mosque of Karanganyar in the year 2020, The research method is descriptive qualitative which effort to elaborate the process of these two learning methods. The results of this study are (1) the Iqro’’ method was effective to encourage self-motivation to recite Al-Qur’an (2) the method of tsaqifa was effective the help the learners learn the Qur’an. (3) The integrated method between Iqro’ and Tsaqifa give much beneficial for the learners. They are able to learn Qur’an easily and having much confidence and self motivation.